Effect of ultrasonication treatment on structural, physicochemical and bioactive properties of pasteurized rosehip (Rosa canina L.) nectar - Atalar, Ilyas; Sarıcaoğlu, Furkan Türker; Odabas, Halil I.; Yilmaz, Volkan A.; Gul, Osman (Elsevier, 2020)
The effect of ultrasonication process (US) on the physical and bioactive properties of pasteurized rosehip nectar was investigated. In order to solve sedimentation problem, two amplitude levels (50 and 100%) and different treatment times (5, 10, 15 and 30 min) were applied to rosehip nectars. Mean particle size decreased as amplitude and treatment time increased. US treatment caused to increase in redness and yellowness values of nectars and also color change was found noticeable as 1.9-2.6 at 100% amplitudes. US treated samples showed no sedimentation during storage for 15 days while control sample displayed 74% colloidal stability. All samples showed shear-thinning behavior and were characterized as weak gel network. Total phenolic and carotenoid contents and antioxidant activity was increased by US treatment, however, ascorbic acid content decreased. US treatment can be an alternative technology preventing sedimentation problems during shelf life with minimally affecting bioactive and physical properties of rosehip nectar.
Keywords: Ultrasound processing; Fruit juice; Viscosity; Stability; Total phenolics